2017
DOI: 10.1016/j.ejca.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of biomarkers associated with clinical outcomes from the study of lenvatinib in differentiated cancer of the thyroid

Abstract: The lenvatinib PFS benefit was maintained regardless of baseline CAF or BRAF/RAS status. Baseline Ang2 was predictive of PFS in a subgroup of lenvatinib-treated patients, indicating that Ang2 may be predictive of lenvatinib sensitivity. BRAF may be a poor prognostic factor in patients with radioiodine-refractory papillary thyroid cancer. Improved PFS associated with upregulated FGF23 suggests that lenvatinib-induced FGF receptor inhibition contributes to lenvatinib efficacy. Trial registration ID of the main s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 27 publications
3
55
1
2
Order By: Relevance
“…Thyroglobulin levels have also been studied as a tumor marker for DTC (16). In the SELECT trial, baseline thyroglobulin levels were associated with poorer PFS in RR-DTC (17). It has been reported that a shorter thyroglobulin doubling time (<1 year) in patients is associated with a poor prognosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroglobulin levels have also been studied as a tumor marker for DTC (16). In the SELECT trial, baseline thyroglobulin levels were associated with poorer PFS in RR-DTC (17). It has been reported that a shorter thyroglobulin doubling time (<1 year) in patients is associated with a poor prognosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lenvatinib cannot be simply said to be a promising Another index of efficacy in thyroid carcinoma is serum Tg [14]. Whereas morphologic assessment is routinely adopted to evaluate treatment efficacy, the role of serum Tg is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lenvatinib was associated with antitumor activity in advanced glioblastoma (32). Biomarkers predicting the efficacy of antiangiogenetic agents include p-VEGFR2 expression in advanced breast cancer and angiopoietin 2 expression in differentiated cancer of the thyroid (33,34). Further investigations are warranted to determine which tumors respond to antiangiogenesis inhibitors, including lenvatinib.…”
Section: Discussionmentioning
confidence: 99%